Pengaruh Strategi Pengelolaan Keuangan Dan Manajemen Risiko Keuangan Terhadap Kondisi Keuangan Dalam Kehidupan Sehari-Hari Bagi Masyarakat Perum 2 Prambanan Kota Tangerang - Ridha Raya Dinayah; Aulia Kaila Rohmah; Alya Fitria Sari; Ela Nurlaela; Yanti Susanti (LKP KARYA PRIMA KURSUS, 2025)
Abstract This study aims to analyze the influence of financial management strategies and financial risk management on the financial condition of housewives in daily life. A quantitative approach with a descriptive method was used, implemented through a financial literacy-based educational training involving 40 housewives as respondents. Data were collected using pre-test and post-test questionnaires, then analyzed using multiple linear regression tests, t-tests, F-tests, and the coefficient of determination with the assistance of IBM SPSS Statistics 25. The results show that financial risk management strategies (X2) have a significant influence on the financial condition (Y), both before and after the training. In contrast, financial management strategies (X1) do not show a statistically significant effect, although there was an increase in the average score. However, when tested simultaneously, the combination of strategies X1 and X2 has a positive and significant influence on the respondents' financial condition. These findings emphasize the importance of synergy between financial planning and risk mitigation in strengthening household financial resilience.